The impact of Maize (Zea mays L.) and it uses for human development: A review - Adiaha, Monday Sunday (International Journal of Scientific World, 2017)
Corn possesses significances nutrients, minerals and vitamins, which provides nutrition in animal diet as well as man. Its health benefits have been countless since the prehistoric era. Maize has been revealed to have the potential to sustained human health-related cases, raise standard of living of farmers, served as a soil fertility indicator crop, generate income and increase food-crop production for the increasing human population. Industrial utilization of maize has been shown to include: wet milling, production of bio-fuel, ethanol and other sub-byproducts.